Neoadjuvant chemotherapy for initially unresectable intrahepatic cholangiocarcinoma. Issue 7 (31st August 2017) - Le Roy, B; Gelli, M; Pittau, G; Allard, M -A; Pereira, B; Serji, B; Vibert, E; Castaing, D; Adam, R; Cherqui, D; Sa Cunha, A
Abstract: Background: Locoregional extension of intrahepatic cholangiocarcinoma (ICC) at the time of diagnosis results in a low resectability rate and poor prognosis. The aim of this retrospective study was to assess the efficacy of neoadjuvant chemotherapy for locally advanced ICC. Methods: All consecutive patients with ICC between 2000 and 2013 were included prospectively in a single-centre database and analysed retrospectively. Patients with locally advanced ICC considered as initially unresectable received primary chemotherapy, followed by surgery in those with secondary resectability. Results of patients who underwent surgery for locally advanced ICC were compared with those of patients with initially resectable ICC treated by surgery alone. Results: A total of 186 patients were included in the study. Of 74 patients with locally advanced ICC, 39 (53 per cent) underwent secondary resection after a median of six chemotherapy cycles. Patients in this group were younger ( P = 0·030) and had more advanced disease than those who had surgery alone, and presented more frequently with lymphadenopathy ( P = 0·010) and vascular invasion ( P = 0·010). Postoperative morbidity and mortality were no different between the groups. The median survival of patients who had surgery after chemotherapy was 24·1 months, and that of patients who had surgery alone was 25·7 months ( P = 0·391). Conclusion: Patients with locally advanced ICC treated by surgery following neoadjuvant chemotherapy had similar short- and long-term results to patients with initially resectable ICC who had surgery alone. Neoadjuvant chemotherapy as a first-line treatment for locally advanced ICC may be an effective downstaging option, facilitating secondary resectability in patients with initially unresectable disease. Abstract : Option to increase resectability